Introduction to broadband communication systems - Akujuobi, Cajetan M.; Sadiku, Matthew N. O. (Boca Raton [Raleigh, NC] Chapman & Hall/CRC SciTech Pub., 2008)
This book covers the typical broadband communication network systems. The question of why broadband networks are important in modern-day telecommunications is also covered. As evident from the outline, the book is divided into five parts. The book begins by providing the fundamental concepts of broadband communication systems. Part 1 discusses Internet-based networks-Internet, intranets, and extranets. Part 2 addresses networking technologies-X.25 and frame relay, fiber channel, synchronous optical network (SONET), virtual private network (VPN), integrated service digital network (ISDN), broadband ISDN (B-ISDN), and asynchronous transfer mode (ATM). Part 3 focuses on access networks-digital subscriber line (DSL), cable modem, and passive optical networks. Part 4 deals with wireless networks-wireless data services, personal communications service (PCS), and satellite communications. Part 5 covers network management and network security. The book concludes with networking testing, fault tolerance, and analysis.
Electronic reproduction.
Keywords: Computer networks; Broadband communication systems; Electronic books